Value of preoperative radiotherapy in treatment of squamous cell carcinoma of the esophagus - Jarema, Alina; Kamiński, Marek; Zieliński, Stanisław; Sulikowski, Tadeusz; Majewski, Włodzimierz (Contemporary Oncology/Współczesna Onkologia, 2000)
The purpose of the work was to determine a value of preoperative radiotherapy and radioterapy as a definite paliation in the treatment of squamous cell carcinoma of the esophagus. The material consisted of 41 esophageal resections; 30 with neoadiuvant radiotherapy of 30 Gy compared with 11 without radiotherapy. There was no statistical significance in total survival time in operated groups attributed to performed preoperative radiotherapy – mean 14 months in radiotherapy group versus 12 months in controls (postoperative deaths included). The probability of survival of 18 and 24 month was higher in radiotherapy group than in controls (81% and 40% versus 50% and 25% respectively).